O controle da "lepra" e o papel dos preventórios: exclusão social e interações socioespaciais dos egressos do educandário Alzira Bley no Espírito Santo - Pavani, Elaine Cristina Rossi (2019)
The “leprosy” has always been seen as a threat by society and, for a long time, the only solution to the problem was compulsory isolation. In Brazil, Getúlio Vargas (1934) launches the “National Plan to Combat Leprosy,” which provided for the construction of leprosy asylums in all Brazilian states. Such a plan was based upon the tripod: leprosy asylums (for the infected), dispensaries (for the able to speak) and preventorium (for the indemnitees children). In Espírito Santo, the Pedro Fontes Colony Hospital, also known as Itanhenga Colony and the Alzira Bley Boarding home were built on Cariacica-ES. The Boarding home was inaugurated on April 11, 1937 with the purpose of welcoming the children who were sent there by means of regulatory measures, which established the immediate segregation of the children of leprous people shortly after birth in colony hospitals. The affected people compulsory isolation of due to leprosy and their children in the preventoriums was based on scientific theories (sanitarianism / hygiene / eugenics) that legitimized, and in a context of greater state control over national affairs, through old authoritarian mechanisms and the strength of the State apparatus. As of 1980, the use of Polychemotherapy (MDT) has been advised for the treatment of all people with leprosy in the world. Within this context, there was also the end of the compulsory isolation of the indigent children who inhabited the boarding homes. These, in turn, were (re) introduced into society. The preliminary report of the Secretariat of Human Rights of the Presidency of the Republic (09/25/2012), on the segregated children of "leprosy" parents submitted to the policy of compulsory isolation, that more than 33,689 children were isolated throughout 59 years, a period that lasted the isolation of the children. In Espírito Santo there are more than a thousand children. The hypothesis that guides this study is that the implementation of a public policy of segregation by the State deeply and irreversibly impacted the social life and violated the rights of many children and adolescents admitted compulsorily in the Alzira Bley Boarding home. The objective of this work was to demonstrate the political and spatial strategies used to the social segregation of the leprous population and their healthy offspring in the State of Espirito Santo; to present aspects of the inmates’ life within the preventorial institutions, to characterize the egress population currently and the consequences of segregation on their lives. The methodology employed for the development of the research involves the research bibliographical, documental and empirical research with the application of questionnaires and the life stories reports of the former inmates of the Alzira Bley Boarding home. From this information we were able to trace this population profile, which was (re) introduced in the society after the end of involuntary admission: they are people with low level of education; ready to occupy underemployed jobs or low paying jobs; who settled mostly in neighborhoods close to the Boarding home or in RMGV, presenting a low self-esteem and difficulties to maintain the family relationships.